Effects of rubber plantations on soil physicochemical properties on Hainan Island, China. Issue 6 (23rd September 2021) - Sun, Rui; Wu, Zhixiang; Lan, Guoyu; Yang, Chuan; Fraedrich, Klaus
Abstract: Recent and rapid expansion of rubber [ Hevea brasiliensis (Willd. ex A. Juss.) Müll. Arg.] plantations requires understanding their effects on soil physicochemical properties and soil quality. An ideal testbed for analyzing such land‐use change and its impacts is Hainan Island, the largest tropical island in China, which in recent decades has seen a dramatic expansion in the rubber industry. Based on 14 soil physicochemical properties at two soil depths (0–20 and 20–40 cm), a comprehensive assessment index was established using principal component analysis to assess soil qualities under rubber plantations (RPs; monoculture and intercropping) and five additional land‐use types (areca palm [ Areca L.], eucalyptus [ Eucalyptus loxophleba Benth.] and banana [ Musa L.] plantations, secondary forest, and tropical rainforest [TR]). The following results were obtained: (a) total porosity, ammoniacal N, total P, available P, and soil organic matter were vital soil physicochemical properties contributing to the comprehensive assessment index; (b) the comprehensive assessment indices of RPs were significantly lower than those of TR and areca palm plantation; (c) intercropping improves most soil physicochemical properties in RPs comparing monoculture and intercropped RPs; and (d) redundancy analysis demonstrated that land‐use type interacted with climatic, geographical, and edaphic factors and collectively explained about half of the variation in the soil physicochemical properties across the study area. Deteriorating soil quality by converting TR to RPs and other land‐use types provides another reason to protect TRs, especially on area‐limited islands like Hainan. Core Ideas: Total porosity, ammonium N, total P, available P, and SOM were important properties for soil quality assessment. Intercropping improved soil physicochemical properties in rubber plantations. The soil comprehensive assessment index of rubber plantations lower than tropical rainforest.